(untitled) (Research, Society and Development, 2020)
The objective of the present study was to evaluate the morpho-agronomic parameters, chemical composition and genetic divergence among Manihot sp. access collected in the Curimataú and Cariri micro regions of the State of Paraíba - Brazil. The experiment was conducted in a completely randomized design with 10 access and 8 replicates. Morpho-agronomic characterization was evaluated through 16 agronomic traits and 12 morphological traits. For the chemical evaluation, 11 traits were discriminated. According to the results, access 2 (Monteiro-PB) was considered a tall plant, with larger canopy area with smaller leaves. The access are cylindrical plants with dark green apical leaf and obovate-lanceolate central lobe, straight or zig zag growth, green vein and with the presence of five lobes and terminal branches in the green plants. The branching levels range from 1 to 4, upward or horizontal petiole and reddish green petiole color. The stipules are short and the sinuosity of leaf lobe is smooth. From the chemical variables evaluated in the access of Manihot, the ones that contributed the most to distinguish genotypes were the content of neutral detergent fiber, non-fiber carbohydrates and total carbohydrates. The morpho-agronomic traits together with the chemical composition data serve as a parameter to indicate the possible access to be used in the forage processing, with better nutritional value.